2011
DOI: 10.4271/2011-01-2084
|View full text |Cite
|
Sign up to set email alerts
|

Transient simulation of NOxreduction over a Fe-Zeolite catalyst in an NH3-SCR system and study of the performance under different operating conditions

Abstract: The NO x reduction in an ammonia SCR converter has been simulated by a 1D+1D model for a single representative channel to parametrically study the characteristics of the system under typical operating conditions. An appropriate model has been selected interpreting the chemical behavior of the system and the parameters are calibrated based on a comprehensive set of experiments with an Fe-Zeolite washcoated monolith for different feed concentrations, temperatures and flow rates. Physical and chemical properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…The rate equations taken from [10] have published parameters, which are used directly in the model. The standard and fast SCR reactions remained to be calibrated, and this was completed using emissions cycle data from RICARDO, which contained pre-and post-catalyst NO x concentrations from a 3.0 litre capacity V6 diesel engine fitted with an SCR over the New European Drive Cycle (NEDC) test cycle.…”
Section: Principles Of Scrmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate equations taken from [10] have published parameters, which are used directly in the model. The standard and fast SCR reactions remained to be calibrated, and this was completed using emissions cycle data from RICARDO, which contained pre-and post-catalyst NO x concentrations from a 3.0 litre capacity V6 diesel engine fitted with an SCR over the New European Drive Cycle (NEDC) test cycle.…”
Section: Principles Of Scrmentioning
confidence: 99%
“…are taken from [10]. In these rates, concentrations (C x ) are in moles per cubic metre, θ is the ammonia coverage ratio (i.e., proportion of the catalyst filled with ammonia), Φ is the storage capacity in moles, V is the catalyst volume, C N H3 is the concentration of ammonia in the reactor, R and T are the universal gas constant and temperature respectively, K eq is an equilibrium constant that is given for various NO:NO x ratios, and the set {k ads , k des , E des , γ} are constant parameters to be calibrated.…”
Section: Principles Of Scrmentioning
confidence: 99%
“…Therefore the filling level can be used as indicator for slip estimation which is indeed important for the SCR dosing control. Although a good model prediction quality is achievable in validation (apart from inhibition effects see Sharifian et al [2011]) with regard to the NMPC the model should be improved to further reduce the model plant mismatch. Hence, in addition to the physical based approach a data based extension is requested to improve the model quality.…”
Section: Physical Based Scr Modelingmentioning
confidence: 99%
“…In literature various investigations for modeling and control of the different after treatment devices are presented. The proposed SCR models are in the range from detailed high prediction quality models suitable for system analysis (Sharifian et al [2011]) to control oriented modeling approaches as shown in (Schär et al [2006] and Zanardo et al [2013]). In Willems et al [2007], McKinley and Alleyne [2012] and Hsieh and Wang [2009] different SCR-and an LNT control schemes are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics and performance of Cu-zeolite and Fe-zeolite catalysts have been studied through both engine and reactor experiments [3,5,14]. Numerous SCR models and kinetic studies have also been published for different formulations including Cuzeolite and Fe-zeolite catalysts [6,8,17,20,24]. However, most of the modeling studies focused on only the SCR inlet and outlet emission measurements without considering the spatial measurements in the channels.…”
Section: Introductionmentioning
confidence: 99%